Software-Defined Value Stream Process Systems - Max Goebels; Alexander Schulte; Patrick Georgi; Fabian Heimberger; Jannik Schwalm; Oliver Liewerenz; Adrian Schäfer; Jürgen Fleischer; Alexander Verl; Hans-Christian Möhring; Volker Schulze; Sven Matthiesen; et al. (Machines)
The increasing volatility of the markets and the growing demand for customized products are challenges for future production to ensure maximum flexibility and adaptability. This paper introduces software-defined value stream process systems (SVPSs), a novel approach that extends the concept of software-defined manufacturing into autonomous, reconfigurable production systems. SVPSs establish a cyber–physical chain that links product features to requirements, enabling their fulfillment through modular machine and process hardware. A modular construction kit of individually combinable hardware and associated software modules is presented. These modules are coordinated via a digital process chain that enables holistic simulations, optimizations, and planning based on a Digital Twin. This system is based on software-defined manufacturing but extends it into autonomous reconfigurable machines. By enabling virtual planning and commissioning of entire production lines, the SVPS concept provides an efficient and adaptable solution to meet the demands of volatile markets.